Hadith Prohibition of Prohibiting Habaib in Social Media - Surur, Aziz Miftahus; Syam, Nur; Roibin, Roibin (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
The difference in mindset between individuals triggers conflict. The right attitude is the main factor causing conflict. Social media, as a means of communication and information, plays an essential role in presenting information. Criticism that results in criticizing the habaib is a new problem that needs attention. Research on the hadith regarding the prohibition of attacking habaib on social media needs to be studied to describe the meaning of the hadith conveyed. This study aims to provide readers with an understanding of the importance of understanding textual and contextual hadiths and the methods used by classical and contemporary scholars in practising the Prophet's traditions. The technique used in this study was library research. The primary sources in this study were the book Mirqat al-Mafatih by 'Ali al-Qari and Kitab al-Jami' al-Sahih by Imam al-Bukhari. The study's results stated that criticizing habaib on social media was an ethical violation. In addition, disgraceful acts also include prohibited actions in Islamic law. A history of hadith strengthens the position of habaib as part of ahl albayt. Habaib has the right to be respected and glorified like humans with a respected conscience.